2008
DOI: 10.1007/s00423-008-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term experience on surgical treatment of alveolar echinococcosis

Abstract: Curative surgery for AE is feasible if the parasitic mass is removable entirely. The earlier the stage, the more frequent is R0 resectability. The observance of a minimal safe distance increases the rate of R0 resections. The benefit of palliative surgery is uncertain due to favorable long-term results of medical treatment alone. However, necrotic tissue is at risk of bacterial superinfection, which can cause life-threatening sepsis. Palliative surgery is an option to treat complications, which could not be ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 27 publications
2
48
1
7
Order By: Relevance
“…On the other hand, Kawamura et al (52) reported that long-term survival rates approached 100% in cases that underwent complete resection with a surgical margin below 1 cm (R0) and received chemotherapy after surgery. Nevertheless, it is also reported that in some patients treated by "curative" resections, recurrence may occur after several years (18,53). Thus, it is concluded that long-term, possibly life-long, follow-up is required (53).…”
Section: Follow-up Of Patients With Alveolar Echinococcosismentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Kawamura et al (52) reported that long-term survival rates approached 100% in cases that underwent complete resection with a surgical margin below 1 cm (R0) and received chemotherapy after surgery. Nevertheless, it is also reported that in some patients treated by "curative" resections, recurrence may occur after several years (18,53). Thus, it is concluded that long-term, possibly life-long, follow-up is required (53).…”
Section: Follow-up Of Patients With Alveolar Echinococcosismentioning
confidence: 99%
“…Nevertheless, it is also reported that in some patients treated by "curative" resections, recurrence may occur after several years (18,53). Thus, it is concluded that long-term, possibly life-long, follow-up is required (53). In this regard, sectional imaging techniques (US, CT, and MRI) play an important role in monitoring the patients.…”
Section: Follow-up Of Patients With Alveolar Echinococcosismentioning
confidence: 99%
“…These compounds inhibit parasite proliferation, making them parasitostatic, but they do not cure the disease, meaning patients have to undergo chemotherapy for extended periods of time, often lifelong. Although benzimidazoles clearly have beneficial effects for patients in terms of life quality and survival, the current treatment results in high costs and elevated risk of adverse effects (12)(13)(14)(15)(16)(17). A number of compounds have been investigated in the past as treatment alternatives for AE, using in vitro-cultured parasites and/or in vivo rodent models.…”
Section: T He Disease Alveolar Echinococcosis (Ae) Is Caused By Infecmentioning
confidence: 99%
“…2 Nonradical resections (R1/2) are not recommended, as they do not provide a survival advantage when compared with long-term conservative treatment. 6 A search of the PubMed and Scopus databases with the keywords alveolar echinococcosis, laparoscopic, robotic, and liver resection found no publications devoted to performing the surgery, either with robotic devices or by laparoscopy. Laparoscopic intervention with alveococcosis of the liver is mentioned in one publication as a diagnostic method.…”
Section: Discussionmentioning
confidence: 99%